The Relationship Between Sleep Quality and Emotional Stability in Final Year Students at Padang State University - Jannah, Alifah Desita; Auliandra, Azkiya; Nisrina, Indira Dwi; Wahyudi, Muhammad; Rapika; Disy, Vashti Mutiara (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
This study is a quantitative study that aims to describe the relationship between sleep quality and emotional stability in final year students at Padang State University. The research subjects were 43 people obtained through purposive sampling technique with the criteria of final year students who are working on their thesis. Data collection used the adopted sleep quality scale consisting of 17 items with a reliability value of 0.804 and the adopted emotional stability scale consisting of 25 items with a reliability value of 0.962. Data analysis used Pearson's Product Moment to test the relationship between the two variables. The results showed a significant relationship between sleep quality and emotional stability with a p value = 0.039 (p <0.05). The negative correlation coefficient of -0.317 indicates that the worse the sleep quality, the lower the emotional stability. Categorization shows that the quality of sleep of students is in the moderate category, while emotional stability tends to be low. The results of this study indicate that there is a relationship between sleep quality and emotional stability of final year students at Padang State University.